A prospective study of leisure‐time physical activity and risk of incident epithelial ovarian cancer: Impact by menopausal status. Issue 4 (22nd September 2015) - Huang, Tianyi; Eliassen, A. Heather; Hankinson, Susan E.; Okereke, Olivia I.; Kubzansky, Laura D.; Wang, Molin; Poole, Elizabeth M.; Chavarro, Jorge E.; Tworoger, Shelley S.
Abstract : Despite multiple hypotheses for a protective effect, epidemiologic findings are inconsistent regarding the association between physical activity and risk of ovarian cancer. Considering physical activity assessment at different times of life, including pre‐ and postmenopause, may be important for explaining these discrepancies. Therefore, we examined the risk of ovarian cancer according to total, premenopausal and postmenopausal physical activity among 85, 462 women from the Nurses' Health Study and 112, 679 women from the Nurses' Health Study II. Leisure‐time physical activity was prospectively assessed about every 2–4 years using validated questionnaires, and characterized as metabolic equivalent task hours per week (MET‐hr/week), which combines exercise duration and intensity. Multivariable Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for these associations. We identified 815 incident epithelial ovarian cancer cases during 24 years of follow‐up. A modestly increased ovarian cancer risk was observed for high levels of total cumulative average physical activity and a suggestively increased risk for low activity. Compared to 3–9 MET‐hr/week, HRs (95% CIs) were 1.26 (1.02, 1.55) for ≥27 MET‐hr/week (equivalent to 1 hr/day of brisk walking) and 1.19 (0.94, 1.52) for <3 MET‐hr/week. This association was limited to premenopausal physical activity [comparable HR (95% CI) of 1.50 (1.13, 1.97) and 1.29 (0.95, 1.75), respectively]. Postmenopausal physical activity was not associated with risk. Our data do not support a protective role of physical activity for ovarian cancer. The increased risk associated with physical activity during premenopausal years and the underlying etiology require further investigation. Abstract : What's new? Previous studies have reported mixed associations between physical activity and ovarian cancer, including positive associations in some prospective studies. In the present investigation, which represents one of the largest studies to date on the topic, an increased ovarian cancer risk was observed for both low and high levels of premenopausal physical activity. Postmenopausal physical activity, by contrast, was not associated with risk. Further analyses on histologic subtype and luteal progesterone suggest that obesity and ovulation may play a role in the associations for low and high activity, respectively.